2009
DOI: 10.1186/1471-2458-9-401
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of cervical cancer vaccination in preadolescent Canadian females

Abstract: Background: Despite the fact that approximately 70% of Canadian women undergo cervical cancer screening at least once every 3 years, approximately 1,300 women were diagnosed with cervical cancer and approximately 380 died from it in 2008. This study estimates the effectiveness and cost-effectiveness of vaccinating 12-year old Canadian females with an AS04-adjuvanted cervical cancer vaccine. The indirect effect of vaccination, via herd immunity, is also estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
21
0
3
Order By: Relevance
“…These results were in line with the results from previous studies in other countries, which confirmed that the ICER of HPV vaccination has been considered to be sensitive to vaccine price [68,69] and discount rate [70][71][72]. Regarding duration of protection, since most of the long-term effectiveness of the vaccine has not been obtained yet, the authors were forced to use assumptions and/or intermediate outcomes for their model.…”
Section: Discussion and Limitationsupporting
confidence: 89%
“…These results were in line with the results from previous studies in other countries, which confirmed that the ICER of HPV vaccination has been considered to be sensitive to vaccine price [68,69] and discount rate [70][71][72]. Regarding duration of protection, since most of the long-term effectiveness of the vaccine has not been obtained yet, the authors were forced to use assumptions and/or intermediate outcomes for their model.…”
Section: Discussion and Limitationsupporting
confidence: 89%
“…The HPV vaccine cost per dose including administration was $85. QALY-weights and unit costs were taken from the literature [25,26,[40][41][42][43][44][45][46][47][48] (see Supplementary Table 2). …”
Section: Parameter Valuesmentioning
confidence: 99%
“…A previously developed lifetime Markov cohort model with a 1-year cycle simulating the natural history of oncogenic HPV in cervical cancer (normal, HPV infection, cervical intraepithelial neoplasia [CIN], cervical cancer, cervical cancer deaths, other deaths) and the effect of screening and vaccination was adapted to reflect the Taiwanese settings [20,23,24]. An additional component to the initial model was appended by Demarteau and Standaert [25] to account for the low-risk HPV infections (including HPV types 6 and 11) that may result in CIN1 and/or GW.…”
Section: Model Structurementioning
confidence: 99%